Perancangan Dan Analisa WAN Dengan Menggunakan Teknologi Frame relay: Studi Kasus Pada PT.XYZ - Fuad Mumtaz (Jurnal Informatika dan Bisnis, 2013)
This research was conducted to determine and design the network Wide Area Network (WAN)for PT. XYZ by taking into account scalability. Where the research methods used include thecollection of data including user needs, analysis of the network according to user needs, libraryresearch, network design, simulation and testing, and evaluation of network design simulationresults. A comparison of WAN technology based on the needs of users it could be concluded thatthe appropriate Frame Relay technology is used to connect headquarters, branch offices, andfactories at PT. XYZ.